2018
DOI: 10.1159/000491544
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Molecular Mechanisms of Platelet-Rich Plasma in Ameliorating Liver Fibrosis Induced by Dimethylnitrosurea

Abstract: Background/Aims: Hepatic fibrosis is a wound-healing process in the chronically injured liver. Clinical application of platelet-rich plasma (PRP) is of considerable interest for wound healing and regeneration. In view of the regeneration effect of PRP, we designed this study to explore the hypothesis that PRP could play a role in improving the biochemical and molecular changes that occur in liver fibrosis induced by dimethylnitrosamine (DMN) in rats. Methods: Four groups were studied: control, PRP control, DMN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…Afterwards Jezequel and coworkers conducted a pioneering study on various aspects of NDMA-induced hepatic fibrosis with special emphasis to pathophysiology and immunohistochemistry and demonstrated that it is a good and reproducible animal model, and appropriate for the study of the early events associated with the development of hepatic fibrosis 4852 . Furthermore, the model has been employed recently to investigate various aspects of the molecular pathogenesis of hepatic fibrosis and to study therapeutic approaches including the arrest of activation of stellate cells 5360 . Over the last 20 years, we have extensively studied various biochemical and pathophysiological aspects of the pathogenesis of NDMA-induced hepatic fibrosis in rats and mice involving glycoprotein metabolism 17 , collagen biosynthesis and metabolism 46 , LDH isoenzymes 61 , biochemical abnormalities 62 , oxidative stress and osteopontin 10,63–65 , hyaluronic acid and hyaluronidase 66,67 , mineral and trace element metabolism 68–70 , antioxidants 10,71,72 and gene therapy 13,73,74 , lysosomal fragility 75,76 , and the role of metalloproteinases 14,77,78 .…”
Section: N-nitrosodimethylamine-induced Hepatic Fibrosis and Liver CImentioning
confidence: 99%
“…Afterwards Jezequel and coworkers conducted a pioneering study on various aspects of NDMA-induced hepatic fibrosis with special emphasis to pathophysiology and immunohistochemistry and demonstrated that it is a good and reproducible animal model, and appropriate for the study of the early events associated with the development of hepatic fibrosis 4852 . Furthermore, the model has been employed recently to investigate various aspects of the molecular pathogenesis of hepatic fibrosis and to study therapeutic approaches including the arrest of activation of stellate cells 5360 . Over the last 20 years, we have extensively studied various biochemical and pathophysiological aspects of the pathogenesis of NDMA-induced hepatic fibrosis in rats and mice involving glycoprotein metabolism 17 , collagen biosynthesis and metabolism 46 , LDH isoenzymes 61 , biochemical abnormalities 62 , oxidative stress and osteopontin 10,63–65 , hyaluronic acid and hyaluronidase 66,67 , mineral and trace element metabolism 68–70 , antioxidants 10,71,72 and gene therapy 13,73,74 , lysosomal fragility 75,76 , and the role of metalloproteinases 14,77,78 .…”
Section: N-nitrosodimethylamine-induced Hepatic Fibrosis and Liver CImentioning
confidence: 99%
“…TGF-β is one of the main drivers of fibrosis. Because PRP has shown an antifibrotic potential in epidural and liver fibrosis, 24,46 how TGF-β in PRP affects the fibrosis stage of AC is still controversial. Fourth, the stage of disease may vary among patients; however, the stage could be regarded as freezing or inflammatory in that most of the patients had unmanageable pain that was mainly associated with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…No previous study was associated with the effect of PRP on the liver. Salem et al described the regenerative impact of platelets in the liver of adult male Wistar rats, which comprises three pathways: a direct impact on hepatocytes, a favorable impact on liver sinusoidal endothelial cells, and a collaborative impact on Kupffer cells [29]. Therefore, it was proposed that the expansion of platelets induced by platelet transfusion would enhance liver functions in patients with chronic liver diseases in the clinical setting [30].…”
Section: Discussionmentioning
confidence: 99%